Significance of Accuracy Comparison in Real-Time Kinematic and Single Point Positioning On-Board Application in Vehicles - Taufan Zandy Andrian (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2022)
Vehicle tracking using the positioning system that is used today is the single point positioning method implementation, but the accuracy of the method is still inadequate for further features to be applied. Therefore, an accuracy improvement is needed. By applying the Real Time Kinematic (RTK) method which has an centimeter level of accuracy, the IndiCar webapp made by PT. Telkom Indonesia offers further features in driving, such as sudden vehicle movements detection, to accidents indications. Accuracy comparisons can also be made to define how significant the difference in accuracy of the two methods. The tests show quite significant results. At single point positioning, the largest deviation is at 20 m and the smallest at 1.0960 m, while in the RTK method, the largest deviation is at a value of 80 cm while the smallest at 0.92 cm. The standard deviation value is then used in the calculation of accuracy. With CEP calculations, the single point positioning method produces accuracy at 5.4659 m, while the RTK method provides a more precise level of accuracy, with a value of 18.22 cm. These results show that the RTK method can be an alternative, to improve accuracy in the use of positioning systems.